Serum Haptoglobin, Ceruloplasmin and CRP levels: Markers of Diabetic Retinopathy (Global Journal of Medical Research, 2012)
Background : Inflammation has been recognised as a critical contributor to retinal capillary closure, one of the main pathogenic event in diabetic retinopathy. The relationship between acute phase markers of inflammation and diabetic retinopathy was studied. Materials and Methods : 60 Type 2 Diabetes patients attending OPD/IPD of Tertiary care hospital were included. They were divided into three groups of 20 each. Group I: without retinopathy. GroupII: with non proliferative diabetic retinopathy (NPDR). GroupIII: with proliferative diabetic retinopathy (PDR). Results were compared with 20 normal controls. FBS, HbA1c, haptoglobin, ceruloplasmin and CRP were analysed on auto analyzer Hitachi 911(Roche)..
Keywords: Non proliferative diabetic retinopathy (NPDR); proliferative diabetic retinopathy (PDR); acute phase proteins; ceruloplasmin; haptoglobin and CRP